Rethinking the role of sheep in the local development of Patagonia, Argentina - Coronato, Fernando Raul (2016)
Patagonia has the world’s southernmost rangelands, which are among the last to be dedicated to farming. Commercial sheep herding in the area only started 100–120 years ago and thrived until the 1930 world crisis, triggering the rapid colonization of grasslands of diverse productivity. Besides this agronomic diversity, natural hazards such as droughts or heavy snowfalls associated with the vagaries of economic policies have always made sheep farming in Patagonia a very uncertain activity. Consequently, sheep gradually lost ground as the leading socio-economic activity to oil and gas production, fishing, and lately tourism. Things worsened during the last quarter of the 20th century to the point where the contribution of agriculture to the regional gross domestic product is today less than 5%. However, sheep farming is the only activity that ensures the occupation, even sparse, of the region and, owing to its pioneer character, it still plays a major part in Patagonian identity. Thus, we believe that mutton and wool production still have a role to play in the future of the region, although we argue that this issue would take the form of one of three scenarios that we termed “laissez-faire”, “park” and “sheep” according to the intensity of the decision involved and the funding required. The three scenarios could eventually coexist but long-term sustainability would have the last word.